Validation of the Brief Version of the Intrafamily Relations Assessment Scale in Young People - Silva Rosas, Alejandra Fiorella (2026)
Introduction: Intrafamilial relationships are a fundamental component of psychosocial well-being in youth. However, factors such as parental work overload and domestic violence can weaken these bonds, highlighting the need for valid and reliable instruments to evaluate them. Objective: To examine evidence of validity based on internal structure and reliability of the brief version of the Intrafamilial Relationships Scale among young people in Metropolitan Arequipa. Method: An instrumental study was conducted with 471 participants aged 18 to 29 residing in Metropolitan Arequipa. Results: Eleven items demonstrated adequate content validity. Confirmatory factor analysis supported a two-factor correlated model (Union/Expression and Difficulties) with satisfactory fit indices: χ2/df = 3.235, CFI = .954, TLI = .941, RMSEA = .075, SRMR = .036. Factor loadings ranged from .540 to .825. Likewise, the short version of the ERI proved to be invariant across the sex of the respondents. Furthermore, the Union/Expression dimension exhibited convergent validity with the Family Satisfaction Scale and the Family APGAR. Both the Union/Expression factor (ω = .901) and the Difficulties factor (ω = .743) showed strong reliability. Conclusion: The brief version of the Intrafamilial Relationships Scale demonstrates robust psychometric properties among young people in Arequipa, providing a valid, reliable, and culturally appropriate tool for assessing intrafamilial relationships in this population.